Long-term monitoring of ocelots Leopardus pardalis (Carnivora: Felidae) in Tortuguero National Park, Costa Rica - Arce, Stephanny Arroyo (2025)
Introduction: The ocelot Leopardus pardalis, though currently listed as Least Concern on the IUCN Red List, has a declining population, and faces threats such as habitat loss and fragmentation and hunting across the entirety of its geographical range, from the Southwestern United States to Northern Argentina. Being a cryptic species and with few studies monitoring ocelots over multiple years, there is a lack of information regarding ocelot ecology. Objective: To further understand the behaviour and population dynamics of ocelots within the study area, Tortuguero National Park (45 755 ha), Costa Rica, by analysing data from a long-term camera trapping study (2011-2022). Methods: Individual ocelots were identified using their unique spot markings. Sex ratio, daily activity patterns, and behaviour were evaluated, whilst ocelot minimum age was estimated for each individual and designated as either resident or transient based on the number of consecutive years observed in the study. Results: A total of 30 individual ocelots were identified (12 females, 18 males). The daily activity pattern (nocturnal) and sex ratio (1 : 0.7) were consistent with that described for the species. The movement of one individual from Tortuguero National Park to Pacuare Nature Reserve, 41 km South, highlights the importance of wildlife corridors for the species. The study also revealed evidence of a female ocelot at least 14 years of age. There are very few published occurrences of an ocelot this old in the wild. Scent marking behaviour was also recorded. Conclusions: This is the longest monitoring effort for ocelots in the country, to our knowledge. Our results highlight the importance of and need for further long-term studies of ocelots to enhance understanding of the species and thus promote the conservation of the species and its habitat.